Improving the Compressive Strength of Concrete with Recycled Ground Glass - Ccente, Kevin (2025)
This paper explores the use of recycled ground glass as a partial substitute for sand in concrete mixtures, aiming to enhance its mechanical properties, specifically compressive strength. Mixtures with glass replacements of 15%, 20%, and 25% were developed and tested, evaluating their performance at 7, 14, and 28 days. Experimental results indicate that using 15% ground glass increases compressive strength by 4.91% compared to standard concrete and improves workability without significantly affecting cohesion. In contrast, higher glass percentages increase the mixture's porosity, reducing its density and strength. Furthermore, the economic analysis shows a cost reduction of up to 1.94% with this optimal proportion. The research concludes that incorporating ground glass is a sustainable and economically viable alternative, as it promotes waste reuse and reduces the demand for natural sand, thereby mitigating the environmental impact associated with construction.